Assessing quality of life in patients with ocular disturbances who underwent surgery for non-functioning pituitary adenoma (Ukrainian Journal of Ophthalmology, 2025)
Background: Ocular disturbances play a major role in the clinical course of non-functioning pituitary adenoma (NFPA). Partial or complete loss of sight affects patient quality of life (QoL), leading to increased dependence and poor performance; in addition, it affects the patient’s level of social adaptation. Developing a QoL questionnaire for patients with NFPA having ocular disturbances will allow for longitudinal monitoring of a patient’s condition and assessing quality of provided care.Purpose: To develop and implement a method for assessing quality of life in patients with ocular disturbances who underwent surgery for non-functioning pituitary adenoma.Material and Methods: We retrospectively reviewed the results of diagnostic studies and treatment outcomes among 100 patients with NFPA having ocular disturbances who received treatment at the Transsphenoidal Neurosurgery Department, Romodanov Neurosurgery Institute, during the period from 2017 through 2018. Patients underwent clinical-and-neurological, ophthalmological, otoneurological and neuroimaging examinations. We developed ocular-disturbance score assessment method and QoL scale for patients with ocular disturbances involving a number of indices related to ophthalmological symptoms, as well as to physical, psychic and social status of specific patients.Results: The QoL scale has two subscales, subscale A (15 questions with each question having three possible responses) and subscale B (5 questions with each question having four possible responses), with the questions answered by the patient and the doctor, respectively. With the testing completed, total scores are calculated. A total QOL score of 0–15 is considered a poor (or low) QoL; 16–30, a moderate (or good) QoL; and 31–45, a high QoL. Treatment outcome monitoring and assessment of QoL over time for patients with NFPA having ocular disturbances can be performed by comparison of total pre-treatment and post-treatment scores. Not only is the extent of injury to the optic and oculomotor nerves assessed, but also the impact of physical handicap on the patient’s activities and on his or her functional abilities.Conclusion: Implementing of the method for assessing the quality of life in patients with ocular disturbances with the help of the scale will allow for longitudinal condition monitoring in the course of treatment for patients with NFPA, making it possible to objectify treatment outcomes.
Keywords: non-functioning pituitary adenoma; ocular disturbances; oculomotor disturbances; quality of life scale